Gamma-Butyrolactone Overdose Potentially Complicated by Co-Ingestion of Industrial Solvent N-Methyl-2-Pyrrolidone. Issue 3 (24th June 2020) - Melamed, Jonathan; Gerona, Roy; Blanc, Paul D; Takamoto, Paul; Conner, Stephanie; Goodnough, Robert
Abstract: Gamma-hydroxybutyrate (GHB) is misused as an intoxicant, either alone or concurrently with other substances. Because GHB is illegal, the precursor chemicals 1, 4-butanediol and gamma-butyrolactone are also misused for the same effect, either through pre-ingestion alteration or endogenous metabolism to GHB. We describe a case of a 50-year-old man with a history of polysubstance misuse who experienced an overdose of GHB from gamma-butyrolactone ingestion. The patient also co-ingested a common industrial solvent, N-methyl-2-pyrrolidone (NMP). This co-ingested substance raised theoretical concern of metabolism to a GHB congener, underscoring that the emergence of new psychoactive substance use patterns requires ongoing vigilance and toxicologic confirmation.